Pengembangan Smart Fish Feeding Berbasis Internet of Things pada Budi Daya Ikan Hias - Algifri Prayudha Diwiryo; Agus Wagyana; Junianto, Purbo Dwi; Muhamad Reza Febrian (Spektral, 2025)
Inappropriate feeding and undetected pond leaks are two major problems in ornamental fish farming that can reduce productivity and operational efficiency. This research aims to develop an Internet of Things (IoT)-based Smart Fish Feeding system capable of automating feeding and monitoring pond conditions in real-time. The system consists of an HC-SR04 ultrasonic sensor to detect feed amounts, a JSN-SR04T sensor to measure water levels, and an ESP32-Cam for visual monitoring. This device is also equipped with a Solenoid Water Valve to automatically regulate water levels and can be controlled via an Android application connected to the Firebase service. This research used a qualitative method with an observational approach and rapid prototyping to design and test the prototype directly at the cultivation site. The test results showed that the system was able to carry out feeding schedules accurately and consistently, and produced an average feed weight per second of 16.38 grams. The developed system has been proven to facilitate fish maintenance and pond management, and has the potential to increase efficiency and responsiveness in ornamental fish farming operations.